Expanding roles of RNA-binding proteins in neurodegenerative diseases - Gitler, Aaron D. (Henry Stewart Talks, 2017)
Amyotrophic lateral sclerosis (ALS), Genetic causes of ALS, Role of RNA-binding proteins and stress granules in ALS pathogenesis, Emerging class of RNA-binding proteins with prion-like domains in neurodegenerative disease, Mechanisms by which C9ORF72 mutations cause ALS